Political Affiliation and Media Distrust: Evidence from Stock Market Investors - Luo, Mancy; Manconi, Alberto; Massa, Massimo (Journal of Financial and Quantitative Analysis, 2026)
Abstract Does distrust in politically affiliated media induce a bias in investor beliefs? We study the acquisition of Dow Jones & Co. by News Corporation in 2007 as a shock to the political affiliation of Dow Jones outlets. Following the acquisition, the prices of Republican- (Democrat-) aligned stocks become less sensitive to favorable (unfavorable) Dow Jones Newswires (DJNW) sentiment, consistent with the market attaching less credibility to a politically affiliated source. There is, however, no evidence of change in DJNW sentiment, coverage, or language about Republican/Democrat stocks, suggesting a loss of stock price informativeness. Consistent with this view, a portfolio exploiting the attenuated reaction to DJNW news earns abnormal returns following 2007.